2D finite element analysis for deformation and stability of bamboo reinforced embankment / AAminaton Marto, Badrul Nizam Ismail, Ismail Bakar and Bakhtiar Affendi Othman - Ismail, Badrul Nizam; Bakar, Ismail; Othman, Bakhtiar Affendi; Marto, AAminaton (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2012)
The problem of soft clay is associated with low bearing capacity and high compressibility. The improvement and stabilization of these soils usually involve expensive soil improvement method. A research has been carried out on the use of locally available bamboo, laid in 1 m square pattern, for reinforcing the soft soil before a 3 m embankment was constructed. The bamboo reinforced embankment, constructed at the Research Centre of Soft Soils (RECESS), Universiti Tun Hussein Onn Malaysia (UTHM), was simulated using a two dimensional (2D) finite element analysis. The purpose of this analysis is to evaluate the deformation and stability of the embankment. The evaluation of deformation and stability are important since the embankment is situated on the soft soil and consists of sloping surface at both sides. It is found that for deformation analysis, it is largely depends on the parameters of Soft Soil Creep model while for stability analysis, the performance of the model simulation largely depends on the parameters of Mohr-Coulomb model. The results from the analysis show that bamboo reinforced embankment performs better in terms of both stability and deformation.